Kürschners Deutscher Literatur-Kalender 2012/2013 : Achtundsechzigster Jahrgang - Schniederjürgen, Axel (De Gruyter, 2012)
The 68th edition, reliably documenting the contemporary literary scene in German-speaking countries, records some 12,000 authors. Without expressing literary critical judgements, it presents since more than 130 years living authors who write in German, whatever their nationality or geographical location may be. Entries provide information on address, biographical data, membership in literary organizations and associations, literary awards as well as each writer's publications. The extensive appendix presents, among others, translators of literature, publishing houses, literary awards, associat.